Hubungan Penggunaan Sumber Informasi Kampanye Dan Partisipasi Politik Pada Kasus Pilpres 2014 Di Kecamatan Cibinong Bogor - Layung Paramesti Martha; Amiruddin Saleh; Parlaungan Adil Rangkuti (Institut Pertanian Bogor, 2015)
Indonesian presidential election campaigns had been held by the candidates and the campaign team respectively from June, 4th-July, 5th 2014. This study was aimed to know the extent of utilization of communication channels both mass media and social media (new media) as source of information, compared with interpersonal communication channel, and how the level of utilization of the information sources by voters during the political campaign influenced the level of political participation in Cibinong. This study had been conducted in September-Oktober 2014 at Sub-District of Cibinong, Bogor Regency. A number of 200 people were chosen as respondents by using purposive sampling technique. The collected data were analyzed with Spearman’s Rank correlation test. Results showed that political participation in the engagement of campaigns as well as the surveillance were poor, while the participation in voting was quite good. In the variable of demographic characteristics, a negative significant correlation was found between political affiliation and the campaign engagement and so between the birthplace and voting engagement. On the contrary, the variable of age, income, and education had no correlation with all dimensions of the campaigns engagement. All dimensions of demographic characteristics including sex, birthplace, and environment had a significant negative correlation with political participation. The indicator of sex and birthplace had a significant negative correlation with the amount of source of information use. The in dicator of birthplace also had a significant negative correlation with the frequent of accessing campaign sources of information. The utilization of campaign sources of information had a significant positive correlation with political participation in the dimension of the engagement in the campaign, voting, and surveillance for the election. Keywords: Political participation, source of information use, political campaign